Yu-Gi-Oh! R. Volume 5, The end of the battle - Itō, Akira (Takahashi, Kazuki, 1961- Yu-gi-oh! R, 2010)
"It's down to the 11th hour as Yugi and Jonouchi fight to save their friend Anzu's soul! Bandit Keith, the ruthless American duelist, challenges Jonouchi to a rematch using his own God Card, the 'Wicked Eraser'! Meanwhile, Yugi faces Yako Tenma, Pegasus's favorite pupil, in a battle which pits god against god!" -- from publisher's web site.